Immediate management dental trauma knowledge of preschool and primary school teachers in Costa Rica - Gutiérrez-Marín, Natalia (2022)
Objective. To determine the degree of knowledge in the immediate management of dental trauma in preschool and primary school teachers in the province of Cartago in Costa Rica. Methods. A cross-sectional observational study was performed. An electronic survey was sent via email to a group of teachers. Sociodemographic and knowledge variables regarding dental trauma care in children were included. Eleven schools participated in the study (6 public and 5 private). The survey was answered by 60 teachers from public institutions and 141 from private schools. A knowledge of score was created, assigning 1 point for correct answers and 0 points for incorrect answers Scores greater than 4 were considered as “adequate knowledge” about dental trauma and its management. Descriptive statistics of the variables and the chi-square tests were performed to determine if there was a difference in the degree of knowledge of the teachers regarding the immediate care of dental trauma according to the sociodemographic variables. Results. Only 24% of the teachers obtained a score higher than 4. In addition, a statistically significant relationship was found between some variables: the older they are, the more experienced they are in teaching, and having witnessed situations of dental trauma, the greater the knowledge of the teachers in this area. Conclusions. Preschool and primary teachers of Circuit 1 of the province of Cartago have, mostly, little knowledge for the immediate care of dental trauma.